Biomaterials for bone regeneration novel techniques and applications - Dubruel, Peter; Van Vlierberghe, Sandra (Woodhead Publishing series in biomaterials., 2014)
In recent decades, there has been a shift from the idea of using biomaterials as passive substitutes for damaged bones towards the concept of biomaterials as aids for the regeneration of a host's own bone tissue. This has resulted in an important field of research and a range of technological developments. This book provides a comprehensive review of the biomaterials available and how they can be applied in bone regeneration. In part one, a wide range of materials are discussed, including calcium phosphate cements, hydrogels, biopolymers, synthetic polymers and shape memory polymers.